Radon Concentration in Al-Gazalia City, Baghdad, Iraq - Ali, Milad J (Al-Nahrain Journal of Science, 2013)
Abstract: Inhalation of indoor radon has been recognized as one of the health hazards. In the present work a set of indoor radon measurements was carried out, in different Iraqi houses in Al-Gazalia city/ Baghdad, built of the same type of building materials. Radon concentration determined by using time–integrated passive radon dosimeters containing CR-39 solid state nuclear track detector. Measurements were carried out from September to November 2011. The results show that, the radon concentrations varied from (38.7 to 200) Bq m-3. The mean values of radon concentrations in second floor hall and first floor of living rooms, kitchens and bathrooms, were: (46.56±9.13), (68.32±8.55), (128.03±21.65) and (168.92±33.52) Bq.m-3 respectively. This data shows that, bathrooms and kitchens have significantly higher radon concentrations and the second floor is lower radon concentration in all dwellings.